2001 α-ketoglutarate-dependent KDM6 histone demethylases epigenetically regulate Interferon Stimulated Gene expression in Lupus. (14th December 2022) - Montano, Erica N; Bose, Moumita; Huo, Lihong; Tumurkhuu, Gantsetseg; Santos, Gabriela De Los; Stotland, Aleksandr B; Wei, Janet; Bairey Merz, C Noel; Martins, Gislaine; Lalani, Sarfaraz; Lawrenson, Kate; Parker, Sarah; et al.
Abstract : The authors have declared that no conflict of interest exists. Objective: To investigate the hypothesis that interferon (IFN) stimulated gene (ISG) expression in systemic lupus erythematosus (SLE) monocytes is linked to changes in metabolic reprogramming and epigenetic regulation of ISG expression. Methods: Monocytes from healthy volunteers and SLE patients at baseline or following IFNα treatment were analyzed by extracellular flux analysis, proteomics, metabolomics, chromatin immunoprecipitation and gene expression. Treatment of SLE monocytes or pristane-treated C57BL/6 mice with GSKJ4 assessed the effects of histone demethylases KDM6A/B on ISG expression. Results: Assessing differences in metabolic programing between monocytes isolated from healthy volunteers or SLE patients, we observed that SLE monocytes exhibit enhanced rates of glycolysis and oxidative phosphorylation, accompanied by an increase in isocitrate dehydrogenase (IDH2) and its product, α-KG. As IDH2 levels correlate with IFN-stimulated genes (ISG) expression, we hypothesized that IFNα priming of monocytes may be driving epigenetic changes at ISG promoters via increased α-KG. We observe decreased H3K27 trimethylation (repressive) and increased H3K4 trimethylation (permissive) at the promoters of ISGs, in keeping with the role α-KG plays as an obligate cofactor for histone demethylases KDM6A and KDM6B, which enhance gene expression by removing H3K27me3 marks at promoters. Inhibition of KDM6A/B resulted in decreased ISG expression both in SLE patient monocytes and in a mouse model of IFN-driven lupus. Conclusion: Our study demonstrates the first link suggesting chronic IFNa/β exposure alters epigenetic regulation of ISG expression in SLE monocytes via changes in immunometabolism, a mechanism reflecting innate immune memory or trained immunity to type I IFN. Importantly, it opens the possibility that drugs targeting histone modifying enzymes such as KDM6A/B may be effective in restoring homeostasis to the IFN network in SLE.